THE INFLUENCE OF BRAND EQUITY AND SERVICE QUALITY TO CUSTOMER LOYALTY OF GARUDA INDONESIA AIRLINES - Maliangkay, Brian (Jurnal Berkala Ilmiah Efisiensi, 2015)
ABSTRACT The research object is Garuda Indonesia Airways. The variable in this research are brand equity and service quality, the indicator of brand equity are brand loyalty, brand personality, brand awareness, brand association, and perceived quality then the indicator of service quality are tangibles, reliability, responsiveness, assurance, and empathy. This research aims to analyze the influence of brand equity and service quality to customer loyalty of Garuda Indonesia partially and simultaneously. 50 loyal customers of Garuda Indonesia had surveyed as respondents. The result showed a positive significant influence of brand equity and service quality to customer loyalty partially and simultaneously. The recommendation for Garuda Indonesia is to keep their performance and have a stronger relation with their customer by Garuda Miles or GFF. Keywords: Brand Equity, Service Quality, Customer Loyalty